Weather, Affect, and Preference for Hedonic Products: The Moderating Role of Gender. (August 2020) - Govind, Rahul; Garg, Nitika; Mittal, Vikas
How and why does the association between weather and hedonic consumption differ between men and women? This article theorizes that women have a stronger affective response to weather conditions, which subsequently induces a larger increase in their hedonic consumption as compared to men. Seven studies show that the relationship between weather conditions and hedonic consumption (food and nonfood items) is differentially mediated by affect for women and men. The studies achieve triangulation by using diverse methodologies (census data, surveys, and experiments), participants (students and nonstudents), measures of independent variables (weather conditions as measured and manipulated), dependent measures (consumption preference and choice), and consumption modalities (food and nonfood).